All‐Optical Thermometry with NV and SiV Color Centers in Biocompatible Diamond Microneedles (Advanced Optical Materials 15/2022). Issue 15 (8th August 2022) - Golubewa, Lena; Padrez, Yaraslau; Malykhin, Sergei; Kulahava, Tatsiana; Shamova, Ekaterina; Timoshchenko, Igor; Franckevicius, Marius; Selskis, Algirdas; Karpicz, Renata; Obraztsov, Alexander; Svirko, Yuri; Kuzhir, Polina
Abstract : Biocompatible single‐crystal diamond needles enriched with nitrogen and silicon vacancy (NV and SiV) color centers in a controllable manner via modified chemical vapor deposition synthesis are employed by Lena Golubewa, Polina Kuzhir and co‐workers (article number 2200631 ) for improved all‐optical thermometry based on the temperature dependence of SiV zero‐phonon‐line (ZPL) peak position, FWHM, photoluminescence lifetime, and ratiometrically determined ZPL intensity. Simultaneous spectrally separated bioimaging with both color centers is performed.